Importance of performance status for treatment outcome in advanced pancreatic cancer - Boeck, Stefan (Baishideng Publishing Group Co., Limited, 2007)
Despite progress in the treatment of advanced and metastatic pancreatic cancer (PC), the outcome of this disease remains dismal for the majority of patients. Given the moderate efficacy of treatment, prognostic factors may help to guide treatment decisions. Several trials identified baseline performance status as an important prognostic factor for survival. Unfit patients with a Karnofsky performance status (KPS) below 70% only have a marginal benefit from chemotherapy with gemcitabine (Gem) and may often benefit more from optimal supportive care. Once, however, the decision is taken to apply chemotherapy, KPS may be used to select either mono- or combination chemotherapy. Patients with a good performance status (KPS = 90%-100%) may have a significant and clinically relevant survival benefit from combination chemotherapy. By contrast, patients with a poor performance status (KPS ≤ 80%) have no advantage from intensified therapy and should rather receive single-agent treatment.